Deep-water Gulf of Mexico Basin: An Overview of Its Petroleum Exploration - F. Hasan Sidi (Berita Sedimentologi, 2001)
The Gulf of Mexico Basin is one of the most prolific petroleum provinces in the world. The present-day deepwater portion of the Guld of Mexico has been explored since mid 1970's. Exploration and development activities have increased significantly during the last couples of years. Since then, over 600 wildcat wells have been drilled in the various deep-water plays in the basin, and industry has leased in excess of 4300 lease blocks covering a cumulative area of more than 38,700 square miles. This activity has been caused by several factors including significant discoveries in deep-water, outstanding reservoir performance in some these discoveries, innovative production techniques, and new Federal royalty relief.There have been 121 discoveries made in the province during the period from 1975 to the end of 1998 with the mean size of these discoveries is 96.5 MMBOE and the largest field found to date is Mars (720 MMBOE). Despite the abundance of drilling and leasing in the basin, some deepwater Gulf of Mexico plays are still in the unproven stage.